Hyperbaric oxygen therapy treatment for the fixation of implant prosthesis in oncology patients irradiated - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Haddad, Marcela F.; Garcia, Idelmo Rangel [UNESP]; Biasoli, Eder Ricardo [UNESP]; Moreno, Amalia (Wiley-Blackwell, 2012)
doi: 10.1111/j.1741-2358.2012.00636.x Hyperbaric oxygen therapy treatment for the fixation of implant prosthesis in oncology patients irradiated Objectives: This study aimed to present a clinical report of an irradiated oncologic patient who underwent hyperbaric oxygen therapy to be rehabilitated with implant-supported prosthesis. Materials and Methods: A 67-year-old man was admitted at Oral Oncology Center (FOA-UNESP) presenting a lesion on the mouth floor. After clinical evaluation, incisional biopsy and histopathological exam, a grade II squamous cell carcinoma was diagnosed. The patient was subjected to surgery to remove the lesion and partial glossectomy. Afterwards, the radiotherapy, in the left/right cervicofacial area of the supraclavicular fossa, was conducted. After 3 years of the surgery, the patient was submitted to hyperbaric oxygen therapy. Then, four implants were installed in patients mandible. Five months later, an upper conventional complete denture and lower full-arch implant-supported prosthesis were fabricated. Conclusion: The treatment resulted in several benefits such as improving his chewing efficiency, swallowing and speech, less denture trauma on the mucosa and improving his self-esteem.
Keywords: radiotherapy; implants; hyperbaric oxygen therapy